The role of gonadotoprins in Alzheimer’s disease: potential neurodegenerative mechanisms - Barron, A.; Verdile, Giuseppe; Martins, R. (Humana Press, 2006)
In addition to the classical role of gonadotropins as a modulator of sex hormone production, it is now becoming apparent that the gonadotropins may have actions within the central nervous system. Evidence is also mounting that age-related increases in levels of the gonadotropin, luteinizing hormone (LH), may exert neuro degenerative effects such as those seen in key cellular and biochemical processes that contribute to the pathogenesis of AD. These processes include the altered metabolism of key proteins in AD pathology, beta amyloid (Aß), and its parent molecule, the amyloid precursor protein (APP). Evidence in the literature suggests that gonadotropins may be involved in processes that contribute to the etiology/pathogenesis of AD such as inflammation, cholesterol homeostasis, and insulin status. Here we examine the potential mechanisms by which gonadotropins could influence neurodegenerative processes. The role of gonadotropins in the brain and potential direct neuropathological effects of elevated gonado tropin levels is an exciting new topic in neuroendocrinology that in turn will lead to the development of novel therapeutic approaches for AD.